Peluang dan Tantangan Adopsi Standar Akuntansi Bisnis dalam Praktik Akuntansi Pemerintahan di Indonesia - Yusup Setiawan; Agus Munandar (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Recent developments in Indonesia’s public financial management have underscored the necessity of aligning the Government Accounting Standards (SAP) with business accounting frameworks such as PSAK and IFRS to enhance transparency, accountability, and legitimacy in managing state finances. The urgency of this study lies in the growing need to adapt governmental accounting systems to global practices while preserving the fundamental characteristics of the public sector, which emphasize service orientation over profit motives. This research aims to critically examine the opportunities and challenges associated with adopting business accounting standards within Indonesia’s public sector accounting framework, as well as to assess their implications for the effectiveness of financial reporting. This study employs a qualitative research design using a literature review approach. Data were collected through an extensive review of scholarly sources, including academic articles, policy documents, and relevant institutional reports. The findings indicate that the shared accrual basis between SAP and PSAK provides a strong foundation for achieving harmonization of accounting standards. However, the implementation process remains constrained by several factors, such as differing objectives between public and business accounting, limited technical capacity among human resources, insufficient integration of financial information systems, and the absence of a comprehensive regulatory framework for convergence.